2003
DOI: 10.1097/01.tp.0000079457.43199.76
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rejection: the next major challenge for pancreas transplant recipients

Abstract: As short-term pancreas transplant results improve and as isolated (PAK or PTA) pancreas transplants gain in popularity, CR will become increasingly common as a cause of pancreas graft loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 17 publications
1
47
0
3
Order By: Relevance
“…They observed that minimal-grade rejection in SPT rarely progressed to more severe grades of rejection, and was not associated with inferior graft survival over a period of 2 years when untreated. Although long-term outcomes are unknown with this approach, Humar et al have shown that chronic rejection is the second most common cause of pancreas graft loss after technical failure [26]. Multivariate analysis showed that the most significant risk factor for pancreas graft loss due to chronic rejection was a previous episode of acute rejection and SPT.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that minimal-grade rejection in SPT rarely progressed to more severe grades of rejection, and was not associated with inferior graft survival over a period of 2 years when untreated. Although long-term outcomes are unknown with this approach, Humar et al have shown that chronic rejection is the second most common cause of pancreas graft loss after technical failure [26]. Multivariate analysis showed that the most significant risk factor for pancreas graft loss due to chronic rejection was a previous episode of acute rejection and SPT.…”
Section: Discussionmentioning
confidence: 99%
“…First, a pancreas allograft is more immunogenic than a liver allograft (29). Therefore, one cannot exclude that addition of the pancreas to the liver may make the cluster graft more immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…As principais causas de insucesso do transplante pancreático incluem as perdas técnicas e a rejeição crônica, que ocorrem em cerca de 13% e 8,8% dos casos, respectivamente (37,38). As perdas técnicas incluem trombose (52%), pancreatite (20,3%), infecções (18,7%), fístulas (6,5%) e sangramento (2,4%) e estão associadas ao índice de massa corpórea do receptor maior que 30 kg/m 2 , ao tempo de isquemia fria do pâncreas maior que 24 horas e à causa de morte cerebral do doador que não seja atribuída a trauma (38).…”
Section: Transplante De Pâncreas E Ilhotas No Dmunclassified
“…Os principais fatores envolvidos na rejeição crônica incluem, além da rejeição aguda, a infecção por citomegalovírus, o retransplante, a modalidade de transplante pancreático (solitário versus simultâneo pâncreas/rim) e uma ou duas incompatibilidades no loci B do Human Leucocyte Antigens (HLA) (37).…”
Section: Transplante De Pâncreas E Ilhotas No Dmunclassified